Mindfulness dan Efikasi Diri terhadap Ketidakpastian Pada Perempuan di Masa Emerging Adulthood - Eustalia Wigunawati; Laurentius Sandi Witarso; Laurentius Purbo Christianto (Pusat Studi Gender, Universitas Kristen Indonesia, 2023)
Emerging adulthood is a transitional period from adolescence to adulthood. During this time, there are many sources of stress due to uncertainty, which can lead to mental health disorders, especially for female individuals. Based on previous literature, mindfulness and self-efficacy against uncertainty can be protective factors for female emerging adults (EA) in facing this period. This study aims to examine the relationship between mindfulness and self-efficacy on uncertainty among emerging adult women. The study utilizes a quantitative approach with a correlational method. Two measurement tools are employed in data collection: the Mindfulness Attention Awareness Scale (MAAS) and the Self-Efficacy on Uncertainty Scale. The participants of this study consist of 121 female students aged between 18 and 25 years, distributed in Jakarta. The results of the study indicate a positive and significant relationship between mindfulness and self-efficacy on uncertainty. The higher the level of mindfulness among emerging adult women, the higher their self-efficacy on uncertainty, and vice versa, the lower the level of mindfulness, the lower their self-efficacy on uncertainty. The variation in mindfulness can account for 12.96% of the variance in self-efficacy on uncertainty, and vice versa, the variation in self-efficacy on uncertainty can explain 12.96% of the variance in mindfulness.